Structural stress analysis and surface settlement study of a subway station in Beijing. Issue 5 (October 2021) - Gangli, Yang; Le, Chen; Nan, Liu; Ming, Jiang; Jili, Feng
Abstract: Taking a PBA construction method station of Beijing subway as the engineering background, Simulation of station construction process by MIDAS / GTS NX finite element software, and compare the simulation results with the on-site monitoring data. The stress of steel tube column and side pile, the main load components of the station, and the surface settlement caused by construction are analyzed. The analysis results show that (1)During the second lining construction stage, the axial force increments of steel tube columns and side piles are the largest, and the axial force increments account for 59.10 % and 51.98 %, respectively. This stage is the key stage to control the axial force;(2)The horizontal displacement curves of steel tube column and side pile show 'bulging' form, and the maximum value is located near the middle of steel tube column and side pile;(3)The transverse surface settlement is symmetrically distributed along the center line of the station, and the maximum value is 47.9 mm, which is located near the center line of the station. The larger settlement is mainly distributed in the range of 20 m from the center line of the station.